Peningkatan Kemandirian Belajar Mahasiswa di Masa Pandemi Covid-19 melalui Penerapan Blended learning pada Mata Kuliah Evaluasi Proses dan Hasil Belajar di Universitas Negeri Malang - Sri Handayani; Annisya’ Annisya’; Andy Prasetyo Wati (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang)
Because of the Covid-19 pandemic, learning was carried out online (online). With online learning, students are required to be independent and learn. Increasing independent learning can be done using Blended Learning. This learning concept is learning designed by combining offline and online learning. The method used in this research is descriptive qualitative by providing an open survey to respondents who are participants of the course. From the results obtained, the learning independence possessed by students in the Process Evaluation and Learning Outcomes course is very high.DOI: https://dx.doi.org/10.17977/UM014v13i22020p152